Immunization as an entry point for primary health care and beyond healthcare interventions—process and insights from an integrated approach in Lebanon - Kapuria, Bhrigu; Hamadeh, Randa S.; Mazloum, Farah; Chaalan, Kassem; Aung, Kyaw; Higgins, Ettie; Kanaan, Wafaa; Tohme, Tatiana; Kamal, Doaa; Khoury, Christina E.; Syed, Sabin (Frontiers in Health Services, 2023)
Integrated healthcare systems are continually pitched as major contributors towards better distribution of health outcomes and enhanced well-being. Under emergency conditions, integrated healthcare services can guarantee better access to the target population. In recent years, several crises, i.e., economic collapse, the fuel crisis, the Beirut blast, a large refugee population, and the COVID-19 pandemic, in Lebanon have led to a major shift in the health-seeking behavior of the communities, with preventive services being downprioritized despite being available and curative healthcare services being sought out as late as possible. An extensive drop in immunization coverage and an overstretched public health system presents the risk of Vaccine-Preventable Disease outbreaks and urgent intervention is needed to bridge the immunity gap. The Ministry of Public Health, Lebanon, and UNICEF Lebanon successfully demonstrated the use of an immunization platform as an entry point to reach communities for service delivery, identification and referral, screening, awareness generation, and a host of other services that can be copied for other programs including but not limited to those for Maternal and Child health, nutrition, early childhood development, COVID-19, children with disabilities, social protection, education, health emergencies like cholera, etc., and these can provide bi-directional support to each other. UNICEF along with the MoPH (Ministry of Public Health) has been working towards reaching the most vulnerable population with a bouquet of services through existing immunization touchpoints for favorable healthcare outcomes.